2017
DOI: 10.1016/j.jpain.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effects of Alcohol: A Systematic Review and Meta-Analysis of Controlled Experimental Studies in Healthy Participants

Abstract: This meta-analysis provides robust evidence for the analgesic properties of alcohol, which could potentially contribute to alcohol misuse in pain patients. Strongest analgesia occurs for alcohol levels exceeding World Health Organization guidelines for low-risk drinking and suggests raising awareness of alternative, less harmful pain interventions to vulnerable patients may be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
97
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(109 citation statements)
references
References 65 publications
10
97
1
1
Order By: Relevance
“…This finding suggests a progressive analgesic effect of ethanol along with chronic alcohol consumption. In humans, alcohol is also an effective analgesic that could explain excessive alcohol drinking in those with persistent pain . Hence, the progressive analgesic effect of ethanol that is only seen in male SNI mice may be a driving factor for excessive alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests a progressive analgesic effect of ethanol along with chronic alcohol consumption. In humans, alcohol is also an effective analgesic that could explain excessive alcohol drinking in those with persistent pain . Hence, the progressive analgesic effect of ethanol that is only seen in male SNI mice may be a driving factor for excessive alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…The association between pain and alcohol use is clearly complex, and the mechanisms of comorbidity of chronic pain and AUD are not well understood in humans. There is a literature examining analgesic effects of alcohol (Chung and Wang, ; Hill et al, ; Patberg et al, ; Thompson et al, ; Woodrow and Eltherington, ), and recent empirical work has found acute pain increases the urge to drink (Moskal et al, ). Further, preliminary work indicates greater alcohol consumption is associated with momentary reductions in pain (Carpenter et al, ).…”
Section: Comorbidity Of Problematic Alcohol Use and Painmentioning
confidence: 99%
“…Older laboratory‐based studies have examined analgesic effects of alcohol in humans (Brown and Cutter, ; Cutter et al, ; Cutter et al, ; Stewart et al, ) and have generally found that alcohol reduces acute pain (Thompson et al, ). Expectancies for pain reduction partially explained the effects in these prior studies (Egli et al, ).…”
Section: Clinical Models To Investigate the Intersection Of Aud And Pmentioning
confidence: 99%
“…For example, regular alcohol use has been implicated in the onset and progression of several painful conditions, 10,11 pain intensity has been positively associated with AUDIT total scores, 12 and laboratory pain induction has been shown to increase the urge to drink 13 . Alcohol has also been shown to confer acute analgesia, 14 and, consistent with negative reinforcement models of addiction, 15 amelioration of negative affect has been identified as a key mechanism in the effects of experimental pain induction on motivation to drink alcohol 7,13 …”
Section: Introductionmentioning
confidence: 99%